Controlling shareholders’ equity pledge and corporate innovation investment—empirical analysis based on pharmaceutical manufacturing - Li, Jiawen; Zhao, Xingyu; Wang, Su; Chen, Yuwen (Frontiers in Public Health, 2025)
Enterprise innovation investment is influenced by the actions of innovation subjects, whereas regulating shareholders’ equity pledge behavior facilitates innovation investment and finance but also carries dangers and affects enterprise innovation investment. Methods:This paper builds an unbalanced panel model to empirically analyze the impact of controlling shareholders’ equity pledges on corporate innovation and its heterogeneous characteristics. It also looks at the moderating role of corporate financing constraints and the mediating role of equity incentives, using data from A-share listed companies in China’s pharmaceutical manufacturing industry from 2015 to 2022. Innovation investment is substantially inversely correlated with controlling shareholders’ equity pledge; that is, firms’ creative behavior and intensity are inhibited by equity pledge. Results and conclusions:The results also show that controlling shareholders’ equity commitments have a more pronounced negative impact on enterprises’ ability to innovate than non-state-owned and decentralized equity firms. The relationship between company innovation and the equity pledge of controlling shareholders is somewhat mediated by equity incentives. The relationship between controlling shareholders’ equity promises and enterprises’ innovation is negatively moderated by financing limitations, which also reduces R&D expenditure and stifles innovation.